Sicurezza e prevenzione del terrorismo cosiddetto islamista: il disagio della libertà (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. La nuova retorica della sicurezza - 2. Il terrorismo cosiddetto islamista - 3. Il diritto penale preventivo e la libertà religiosa - 4. Deradicalizzazione e/è laicità - 5. Sicurezza e libertà: per un orientamento costituzionale.Security and Prevention of so-called Islamic Terrorism: Freedom and its discontentsABSTRACT: Security is becoming the priority of the western politics because of the international terrorism, so called Islamic terrorism. The preventive character that the criminal law takes in order to fight it risks hiting the religious freedom of the citizens, misinterpreted as participation to terroristic groups. The risk is high when the prevention measures consist in the deradicalization, read as religious re-education in unfundamentalist direction. In the constitutional State of law, a fair deradicalization has to aim only to the re-education about the separation between politics and religion so as to not prejudice the right of religious freedom.